Social actors, use and environmental conservation in the Ciénega de Chimaliapan, Mexico - Pérez-Ramírez, Carlos-Alberto (2025)
Introduction: the Chimaliapan lagoon is part of the Cienegas de Lerma protected area, in the State of Mexico, due to its importance for the conservation and sociocultural relevance. However, it faces complex environmental problems due to wastewater discharges, the drying up of the body of water, changes in land use, and the limited coordination between the different social actors that have an impact on the area. Objective: the research aimed to analyze the form of interaction of these actors in environmental conservation, identifying their diversity, sectoral area and the degree of interest and influence in the lagoon. Methodology: a documentary analysis and field work were carried out with the application of a survey to different social actors. Conclusions: 31 actors were identified that correspond to the public, social and private sectors, with impact on different sectoral areas such as agricultural production, use and exploitation of water, industrial activities, hunting, tourism, conservation, environmental education, research and human settlements. It is concluded that there are multiple actors with interest in the environmental conservation of the lagoon, but with limited collective articulation to create collaboration networks to strengthen environmental governance processes.